Overlap between ampC and frd operons on the Escherichia coli chromosome. - Grundström, T (1982)
The promoter for the Escherichia coli ampC beta-lactamase gene is shown to be located within the last gene of the fumarate reductase (frd) operon. Evidence is presented that the ampC attenuator serves as the terminator for transcription of this preceding operon. The nucleotide sequence was determined for two proteins that were shown to be encoded by a DNA segment preceding the ampC gene. The two proteins consisted of 131 and 119 triplets and had molecular weights of 15,000 and 13,100, respectively. The twelve COOH-terminal amino acids of the 13,100 molecular weight protein were found to overlap the ampC promoter. Accordingly, a G.C insertion in the promoter gave both increased transcription of ampC and a frameshift in this overlapping gene, resulting in readthrough proteins. Thus, we describe a type of very compact genetic organization of operons in prokaryotes.